Efektivitas Penerapan Metode Pembelajaran Quiz Team Dalam Meningkatkan Motivasi Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam Di Sekolah Menengah Pertama Islam Al-Mukhlisin Seddur Pakong Pamekasan - Dini Hidayati; Moh Fadili Achsani; Kirohman Kirohman; Mita Damayanti; Imam Nawawi (Kariman: Jurnal Pendidikan Keislaman, 2022)
The purpose of this study was to determine the effectiveness of the Quiz Team learning method in increasing student learning motivation in Islamic Religious Education at Al-Mukhlisin Seddur Pakong Islamic Junior High School. This study aimed to determine the effectiveness of the Quiz Team learning method and the increase in student learning motivation in Islamic Religious Education. The focus of this research is: 1) How effective is the Quiz Team learning method in increasing student learning motivation in Islamic Religious Education at Al-Mukhlisin Seddur Pakong Islamic Junior High School? 2) What are the supporting and inhibiting factors in the implementation of the Quiz Team learning method in increasing student learning motivation in Islamic Religious Education at Al-Mukhlisin Seddur Pakong Islamic Junior High School? This study employed a qualitative approach with a descriptive type of research. The results were obtained in the form of descriptive data. The data sources were the principal, Islamic Religious Education teachers, and students. Data collection procedures used were observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and verification. The results of the research conducted by the researcher revealed that, first, it was effective, as evidenced by increased student enthusiasm for learning, active participation during group discussions, and their commitment to completing quizzes. Students became more confident in expressing their opinions and demonstrated a higher enthusiasm for learning than before. Supporting factors for the successful implementation of this method were active student involvement, group collaboration, a varied, engaging and non-monotonous learning format, the active role of teachers who consistently provided direction, motivation, and guidance, and a pleasant learning environment. Inhibiting factors in the implementation of the Quiz Team method included a lack of student self-confidence, lack of teamwork, a less conducive classroom atmosphere, and teacher difficulty in assessing individuals. This research is expected to provide input for teachers and prospective teachers in selecting and implementing learning methods appropriate to their students' needs